ANALISIS SWOT UNTUK MENENTUKAN STRATEGI PEMASARAN USAHA TELUR PUYUH MBAK TIK - Sri Martono; Fitriyanti (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2022)
Background: Marketing strategy is a plan that will be used by a company to conduct marketing and determine the company's goals and objectives. Marketing strategy is also used to carry out sales activities by using communication techniques that aim to provide information to the target audience so that the company's goals can be successful. The marketing strategy is designed to be effective and efficient with easy distribution of messages and minimal effort is spent on these marketing communication activities. Purpose This study aims to determine the marketing strategy that can be applied to the quail egg business, based on the SWOT analysis.Methods: The research method used is descriptive qualitative because it aims to analyze data by describing or describing the situation in the field and at the same time determining the marketing strategy for your quail egg business.Conclusion: The results of this study through SWOT analysis found that the IFAS matrix is in quadrant I so that it can use strengths to take advantage of existing opportunities. The strategy that must be implemented in this condition is to support an aggressive growth policy, and the SWOT matrix can be found in a marketing strategy that can be applied by your quail egg business, namely to be more aggressive in making sales by maximizing technological advances, maintaining product quality, increasing consumer loyalty, maintaining promotional activities, carrying out site renovations, taking good care of quail health, carrying out marketing innovations, and improving service quality.Suggestion: There are still many limitations in this research and need to be developed again for future research agendas. The scope of this research is still small and in a less broad scope because it is only driven by one informant, so that future research can be developed through the addition of variables and the number of objects to be studied